Unfortunate emigrants : narratives of the Donner Party - Johnson, Kristin, 1953- (Utah State University Press, 1996)
The story of the Donner Party remains one of the most tragic and compelling in pioneer history. Johnson gathers many rare early narratives detailing the participants' trying experiences into one of the most accurate accounts to date of this disastrous event.